[tex]\bf -\cfrac{1}{6}+\cfrac{2}{3}\left( 9-\cfrac{3}{4} \right)-\cfrac{1}{2}\impliedby recall\qquad \mathbb{PEMDAS}
\\\\\\
-\cfrac{1}{6}+\cfrac{2}{3}\left( \cfrac{36-3}{4} \right)-\cfrac{1}{2}\implies -\cfrac{1}{6}+\cfrac{2}{3}\left( \cfrac{33}{4} \right)-\cfrac{1}{2}
\\\\\\
-\cfrac{1}{6}+\cfrac{2\cdot 33}{3\cdot 4} -\cfrac{1}{2}\implies -\cfrac{1}{6}+\cfrac{66}{12} -\cfrac{1}{2}\impliedby \textit{LCD of 12}
\\\\\\
\cfrac{-2+66-6}{12}\implies \cfrac{58}{12}\implies \cfrac{29}{6}\implies 4\frac{5}{6}[/tex]